Communication Strategies of the Kedungwaringin Police in Addressing Traffic Violations Involving Electric Bicycles - Deajeng Plantika Sari; Lukmanul Hakim; Lolita Deby Mahendra Putri (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
The increasing use of electric bicycles in rural areas has been accompanied by low legal awareness and frequent traffic violations. In Kedungwaringin Village, many users perceive electric bicycles as informal vehicles that do not require strict compliance with traffic regulations. This study aims to analyze the effectiveness of the educational–persuasive communication strategies implemented by the Kedungwaringin Village police in addressing these violations. A qualitative research design was employed, using in-depth interviews with police officers and electric bicycle users, complemented by field observations of patrol and outreach activities. The findings indicate that the police have adopted educational and persuasive approaches through direct socialization during patrols, the use of social media platforms, and the distribution of informational leaflets. These strategies have successfully increased users’ cognitive awareness and understanding of traffic regulations. However, improved awareness has not consistently translated into sustained behavioral compliance. Many users comply situationally—particularly when police supervision is present—suggesting that educational communication alone is insufficient to produce long-term behavioral change without consistent law enforcement and social reinforcement. The study implies that communication strategies must be integrated with structured enforcement and participatory community engagement to strengthen internalization of safety values. This research contributes to the literature by enriching discussions on police communication strategies in rural contexts, particularly in relation to the emerging issue of electric bicycle regulation and community-based traffic governance.